The impact of COVID-19 infection on ART outcomes: a multicenter retrospective cohort study - Ruiqi Wang; Yaqi Lin; Lixue Chen; Tian Tian; Hongping Wu; Rui Yang; Rong Li; Ping Liu; Jie Qiao (Journal of Ovarian Research)
Abstract Objective This multicenter retrospective study examines the impact of female COVID-19 infection on assisted reproductive technology (ART) outcomes, including clinical pregnancy rates, miscarriage rates, and live birth rates, and further evaluated potential influencing factors associated with these outcomes. Methods Our multicenter retrospective cohort study analyzed 10,140 cycles (2021–2023) from 10 Beijing ART centers, comparing 4,099 cycles from COVID-19-positive women with 6,041 age-matched (1:1.5) COVID-negative controls (pre-pandemic). Outcomes included pregnancy, miscarriage, and live birth rates, analyzed via logistic regression. Results In our study, maternal COVID-19 infection showed no significant association with ART outcomes, including clinical pregnancy, miscarriage and live birth. However, subtle differences were still observed. Among women with prior COVID-19 infection, compared to those with transfers ≥ 90 days post-infection (16.1%), miscarriage rates were significantly higher in the < 30 days (20.5%, p = 0.055) and 30–60 days (20.4%, p = 0.032) groups, whereas no increase was observed in the 60–90 days group (15.3%, p = 0.912). Additionally, advanced maternal age and elevated FSH levels (> 10 mIU/mL) were associated with diminished clinical pregnancy and live birth rates. What’s more, maternal COVID-19 symptoms and medication use did not significantly affect ART treatment outcomes. Conclusions Our results suggest that while maternal COVID-19 infection does not clearly affect overall ART outcomes, embryo transfer within 60 days may increase miscarriage risk. This provides useful guidance for timing treatment during COVID-19 and future public health emergencies. In Brief Our study found that while a history of the female partner’s COVID-19 infection does not significantly impact ART outcomes, miscarriage rates are higher when embryo transfer occurs within 60 days post-infection. We recommend waiting at least 60 days after infection to minimize miscarriage risk.